COVID-19 endemic phase in Finland: An analysis of health policies and vaccination strategy - Tiirinki, Hanna (Elsevier, 2025)
Objectives
To analyze how the vaccines and various measures to control the pandemic affected epidemiological, health and socioeconomic outcomes of COVID-19 in Finland. The focus of the analysis is on the endemic phase of the COVID-19 pandemic.
Methods
The paper provides an overview of Finland's healthcare system, trends in COVID-19 morbidity, mortality and vaccination coverage data, political considerations, interventions to control the pandemic, as well as the economic impact of the pandemic in the endemic phase. Data were collected from various sources, including previous studies, government reports, national statistics and registers and general media.
Results
In Finland, the total number of COVID-19 infections increased significantly during 2022, but the number of serious forms of the disease decreased. The implementation of the vaccination strategy caused a diversity of opinions among authorities and experts. The governing of the pandemic was fully decentralized. Overall, there is a good vaccination coverage of the population. In the endemic phase society returned to live without restrictions.
Conclusions
It seems clear that vaccines played an important role in controlling the pandemic. Overall mortality increased substantially in 2022 causing life expectancy to fall. Moreover, different “excess death” indicators show an increase in 2021 and 2022, but the timing and magnitude of the effect varies. It is relatively safe to conclude that at least part of increase can be attributed to the pandemic, but a more exact conclusion calls for a comprehensive study. Similarly, understanding long covid and designing required intervention calls for more research.